Hormone Therapy as A New Hope for Achondroplasia Patients - Basuki Supartono; Ayola Dewi Utami; Abyanka Rayhan Fuadi; Bintang Bayu Aryandi (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Achondroplasia is a disorder of child bone growth due to gene mutation of growth factor receptor. Short stature is a major problem. Efforts to increase height are still a challenge. The method performed so far is the lengthening of the limbs with various complications and risks of re-surgery. A promising new alternative without surgery is the administration of growth hormone therapy. This review aims to find out the safety and effectiveness of hormone therapy. The review method used is a narrative review. The review results showed that growth hormone therapy is safe and effective. The review concludes that growth hormone therapy has been proven to be safe and effective in increasing the height of achondroplasia patients.